Investigation into acidbasic equilibrium on the surface of oxides with various chemical nature - Danchenko, Yuliya; Andronov, Vladimir; Rybka, Evgeniy; Skliarov, Stanislav (Eastern-European Journal of Enterprise Technologies, 2017)
The acid-base equilibrium on the surface of CaO, MgO, FeO, Al2O3, Fe2O3, SiO2, TiO2 oxides was studied. As a result of the study, the main provisions have been formulated which made it possible to propose models of surface active centers and schemes of their acid-base equilibrium. The acid-base and energy equilibrium parameters of the active centers in the deprotonation reactions were calculated. Regularities of changes in the acid-base and energy parameters of the active centers were determined depending on the nature of the central element of the crystal lattice, the number of OH-groups and the number of hydration. Acidity of all considered types of active centers depends to a large extent on the nature of the central element, namely its charge and coordination number. It was found that with increase in the coordination number of the central elements with the same charge, pKa of anhydrous centers and the value of their Gibbs free energy in deprotonation reactions increase. Acidity of isolated anhydrous centers increases in a direct proportion as the number of OH groups increases. The obtained regularity preserves for the surfaces of all oxides considered. It was shown for all oxides that when the amount of adsorbed water molecules increases, acidity of the active centers of all types increases and this dependence is identical to the growth of acidity with an increase in the number of OH groups. This indicates identity of the nature of acidity growth with an increase in thickness of hydroxyl and hydration surface layers. The obtained results will ensure prediction of oxide filler behavior in compositions and adjustment of operating properties of composite materials